Children with special needs : lessons for early childhood professionals - Kostelnik, Marjorie J (New York : Teachers College Press, 2002)
Bridging the gap between child development and strategies for inclusion, this volume will help early childhood practitioners and pre-service teachers feel better equipped to meet the needs of all the children in their early childhood setting. Each chapter introduces you to a child (ages birth to 8 years) with one or more special needs, including autism, cerebral palsy, Turner syndrome, ADHD, emotional/behavioral disorders, apraxia, Down syndrome, giftedness, and juvenile diabetes. Advocating a holistic view of working with children, each profile includes: a description of the child; an interview with a family member or early childhood professional describing essential facts and historical incidents in the child's life; an epilogue updating the status of the child; information for educators about the special needs covered in the profile; hints for success-teaching strategies for working with children in inclusive classrooms; discussion questions for the classroom; resources for educators and parents; an appendix with guidelines for an IEP (Individualized Education Program)
1. Starting the Conversation: Working with Children Who Have Special Needs -- 2. Andrew: Absorbed with the Particulars -- 3. Rosie: The Girl with the Million-Dollar Smile -- 4. Sara: "A Person's a Person, No Matter How Small" -- 5. Marcus: Gifted and Challenging -- 6. Irina: Learning to Have a Good Day -- 7. Sam: A Complex Child -- 8. Brian: "Just Bursting to Communicate" -- 9. Daniel: Supported by a Team -- 10. Katherine Mary: The Once-Upon-a-Time Girl -- 11. Concluding Our Conversation: Reflections -- App. A. Individual Education Program Process -- App. B. Contents of an Individual Education Program for Young Children
Includes bibliographical references and index
Keywords: Children with disabilities -- Education (Early childhood) -- United States -- Case studies; Early childhood education -- United States -- Case studies